Shallow-water sea cucumbers (Echinodermata Holothuroidea) in Sarangani bay, Mindanao, Philippines with notes on their relative abundance - Pitogo, Kier Mitchel E.; Sumin, Jennelyn P.; Ortiz, Ariel T. (2018)
The Philippines is known for its high diversity of sea cucumbers; however, there is little done on sea cucumber diversity in the southern Philippines. To augment this paucity of information, a rapid survey of the shallow-water sea cucumbers was carried out in three sites in Sarangani Bay by using the transect method for four months in both the seagrass and coral reef habitats. We recorded 21 species of sea cucumbers ? 17 of these species were found in the seagrass beds and 10 species in the coral reef areas. The three most abundant species observed were the Holothuria scabra (29.2%), Bohadschia marmorata (21.2%), and Actinopyga echinites (17.6%) (n=1,969). Aside from some economically important sea cucumbers observed, we also noted rare species such as the Holothuria immobilis and Actinopyga capillata, which only have a few records in the Philippines. We are also the first to document Holothuria isuga in the Philippines, which is previously known only from five localities. The results offer opportunities for sea cucumber studies in the southern Philippines, especially on the biology and ecology of the rare and newly recorded species.